FATORES CRÍTICOS DE SUCESSO NA EDUCAÇÃO SUPERIOR BRASILEIRA - Marcus Vinicius Andrade Lima (Universidade Federal de Santa Catarina, 2012)
This article purports to verify the critical success factors for undergraduate courses and distance. For that sought to explain theoretically how the characteristics of Distance Education (DE) in Brazil and critical success factors in higher education and distance education. This survey collects a set of information that can be used in managerial institutions working with distance education. As a result of research highlights the challenge of turning the key factors in purchase value attributes that are actually used by buyers in their selection process. As the choice may vary depending on personal preferences associated with the products and services available, highlights the importance of performing well on criteria of excellence and regulation of higher education. Were identified by analyzing the critical success factors identified for distance courses eight factors common to the various sources researched. When it comes to undergraduate classroom can be seen that the commonalities in research conducted by several authors identified thirteen points considered important for success. We conclude that the coordinators of undergraduate need to observe what are the critical success factors for courses and seek to serve them for organizational success.